Developmental competence and the induction of ectopic proboscises in Drosophila melanogaster - Percival-Smith, Anthony; Sivanantharajah, Lovesha; Pelling, Jacob J. H; Teft, Wendy A (Development Genes and Evolution, 2013)
Developmental competence is the response of a cell(s) to information. Determination of adult labial identity in Drosophila requires Proboscipedia (PB) and Sex combs reduced (SCR); however, co-ectopic expression of PB and SCR is not sufficient for induction of ectopic adult labial identity, because the developmental information supplied by PB and SCR is suppressed. The evolutionarily conserved LASCY, DYTQL, NANGE motifs, and the C-terminal domain of SCR are sequence elements that mediate some, or all, of the suppression of ectopic proboscis determination. Therefore, the developmentally competent primordial proboscis cells provide an environment devoid of suppression, allowing PB and SCR to determine proboscis identity. SCR derivatives lacking suppression sequences weakly induce ectopic proboscis transformations independently of PB, suggesting that SCR may be the activity required for induction of adult labial identity, as is the case for larval labial identity. A possible explanation for PB independence of SCR in determination of adult and embryonic labial identity is PB operates as a competence factor that switches SCR from determining T1 identity to labial identity during metamorphosis. Lastly, labial determination is not conserved between SCR and murine HOXA5, suggesting that SCR has acquired this activity during evolution.